Research on Simulation Experiment of Underwater Cluster Multi-source Information Fusion. Issue 3 (May 2021) - Ji, Bei; Tao, Mo; Li, Hongrui
Abstract: Intelligent cluster information fusion technology is one of the key technologies to solve systematic cooperative operations in underwater manned and unmanned cooperative operations clusters. In this study, aiming at the multi-node hybrid multi-level hierarchical information fusion architecture and global optimization association algorithm based on cluster formation detection, the test scheme and evaluation method of multi-level information fusion are proposed, and the cluster information fusion simulation test system including sonar system, simulation deduction and evaluation system and multi-source information fusion system is constructed. For the first time, the system comprehensively verified the ability of multi-platform from orientation to positioning in the grouping of fusion algorithm, and proved the correctness and effectiveness of the fusion algorithm, which could greatly improve the accuracy of orientation and distance, and formed a highly credible simulation test evaluation ability. The system is extensible at the same time, and can also be applied to other simulation experiments.